The relationship of music education with phonological and reading skills of pre-school and early school-age children - Tsesmeli, Styliani Ν.; Sotiropoulou, Εleni; Ntente, Εleni (Psychology: the Journal of the Hellenic Psychological Society, 2021)
The aim of the study was to evaluate the effect of the training of morphological awareness of spelling words by 27 students following 4th and 6th grades of a primary school. They were compared with a group of 26 classmates who did not take part in the intervention. All students were assessed via standardized tests of spelling and reading comprehension and non-standardized tests of analogy and meaning of compounds. The intervention included a pre-test, an educational program and a post-test. Experimental material entailed compound words categorized into two conditions of morphophonological transparency (transparent/ non-transparent) and two conditions of compositionality (Modern Greek/Ancient Greek morphemes). Results showed that the systematic exercise of the morphological structure of words improved students' spelling performance in every compound type. Considerably, non-transparent items entailing ancient morphemes received the highest gains, where students presented the lowest performance before intervention. These findings underline the importance of morphological awareness in the acquisition of spelling of morphologically complex vocabulary, whose teaching is important in the highest grades of primary school.